Young nights - Ng, Ken Hsin Li (2018)
Young Nights is a story of change and growth. Zachery meets Kester; both clash in personality, yet they share similar interests in music and night life. Their friendship is tested along the way but the choices they make to stick by each other defines their concept of 'forever' – to be loyal companions to one another.